ANALISIS MAQASHID SYARIAH PERSEPSI DAN PERILAKU MASYARAKAT TERHADAP PROGRAM BANTUAN PANGAN NON TUNAI DESA DI MASA PANDEMI COVID-19 (STUDI KECAMATAN PAMIJAHAN KABUPATEN BOGOR) - Siti Evi Alfiah; Tubagus Rifqy Thantawi; Bayu Purnama Putra (SAHID BUSINESS JOURNAL, 2022)
Socio-economic changes in the community during the COVID-19 pandemic resulted in a weakening of the economy in the community, one of the solutions provided by the government to deal with the socio-economic impact during the COVID-19 pandemic was non-cash food assistance. This study aims (1) to find out how the maqashid sharia perception of the village non-cash food assistance program during the covid-19 pandemic in the Pamijahan sub-district, Bogor district. (2) to find out how the community behaves towards the village non-cash food assistance program during the covid-19 pandemic in the Pamijahan sub-district, Bogor district. This type of research is by using quantitative research that uses a Likert scale, with a sample of 100 respondents. The sampling technique used was purposive sampling with the Tabachic & Fidell method. The analytical method used in this study is multiple linear regression analysis using the IBM Statistical Package for Social Sciences (SPSS) Version 25 Software. The results of this study indicate that the perception of maqasid sharia partially has no effect on the non-cash food assistance program. The behavior of the community partially has a significant effect on the non-cash food assistance program. Simultaneously, the perception variable of sharia maqashid and community behavior has a significant effect on the non-cash food assistance program